2018
DOI: 10.1002/app.46259
|View full text |Cite
|
Sign up to set email alerts
|

Tough, stable spiroacetal thiol‐ene resin for 3D printing

Abstract: Though over 30 years old, 3D printing has seen an explosion of interest in recent years as technology has become sufficiently advanced and affordable, enabling widespread usage, and investigation of the technique as a method of manufacture. However, the materials commonly used for printing applications frequently suffer from poor mechanical properties and are only suitable for prototyping and non-load-bearing objects. We report a stable, tough resin formulation which incorporates spiroacetal molecules into the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 46 publications
1
30
1
Order By: Relevance
“…[ 5–9 ] Introducing alternative crosslinking chemistries to the VAM realm, as well as AM more broadly, is highly desirable as an alternative method to gain access to a wider range of mechanical, thermal, and optical performance. [ 10–14 ] Thiol‐ene‐based polymers are one class of materials that have drawn significant attention owing to their controllable, tunable mechanical properties. [ 15–17 ] This is generally attributed to more uniform molecular networks in thiol‐ene materials, resulting from the step‐growth mechanism of the polymerization reaction.…”
Section: Figurementioning
confidence: 99%
“…[ 5–9 ] Introducing alternative crosslinking chemistries to the VAM realm, as well as AM more broadly, is highly desirable as an alternative method to gain access to a wider range of mechanical, thermal, and optical performance. [ 10–14 ] Thiol‐ene‐based polymers are one class of materials that have drawn significant attention owing to their controllable, tunable mechanical properties. [ 15–17 ] This is generally attributed to more uniform molecular networks in thiol‐ene materials, resulting from the step‐growth mechanism of the polymerization reaction.…”
Section: Figurementioning
confidence: 99%
“…65,66 The flexible thioether linkages in these materials allow for a wide range of T g values [67][68][69][70][71][72][73] and can be exploited to fabricate materials with a broad range of mechanical properties. [74][75][76][77] For example, Childress et al used commercially available thiol and alkene monomers with DLP printing to fabricate crosslinked semicrystalline materials with Young's moduli between 40 and 90 MPa while having an elongation at break between 300% and 800%. 78 At the other end of the mechanical properties spectrum, Warner et al demonstrated the use of diallyl diurethane monomers with multifunctional thiols to synthesize materials with Young's moduli between 400 and 2500 MPa, all with elongation at break exceeding 80%.…”
Section: Materials Compatible With Vp Polymersmentioning
confidence: 99%
“…Photo-induced thiol-ene reactions exhibit the characteristics of both photopolymerization and click reactions, such as spatial and temporal control, high selectivity, insensitivity to oxygen or water, and high yield with no formation of by-products [36]. Due to the unique features of thiol-ene photopolymerization, such as low shrinkage stress and the yielding of homogeneous networks, this type of reaction is very promising for 3D-printing [37,38]. Therefore, thiol-ene resin has been applied to the fabrication of devices via 3D printing [39,40].…”
Section: Thiol-ene Photopolymerization (Tep) Of Methacrylate and Thiomentioning
confidence: 99%